Produksi Telur dan Kualitas Telur Ayam IPB D-1 G7 serta Pendugaan Nilai Ripitabilitasny - Habiburahman, R.; Darwati, S.; Sumantri, C.; Rukmiasih (Jurnal Ilmu Produksi dan Teknologi Hasil Peternakan, 2020)
IPB-D1 is a chicken cross between male F1 PS (PelungxSentul) with F1 female (Kampung x parent stock cobb). The establishment of chicken IPB-D1 aims to produce commercial meat type local chicken with semi-intensive maintenance management. The aim of this research to observe study assesses the performance of egg production and the quality of IPB D-1 chicken eggs and estimates the value of repeatability of production and haugh units of IPB D-1 chicken eggs. The chicken was observed as many as 30 hens IPB D-1 G7 aged 24-36 weeks and eggs as many as 288 eggs. The production and egg quality data were analyzed descriptively and the repeatability values were analyzed with Anova. Egg weight 40 g, Haugh unit value 87 (Very good), egg production 49.22%. The repeatability value of egg production is 0.2 (Moderate) and the repeatability value of the haugh unit is 0.31 (Medium). IPB D-1 Chicken has the potential to be a good dual-purpose chicken.